INVESTIGATION OF THE SUBPOPULATION COMPOSITION OF BLOOD LEUKOCYTES IN ASSESSING THE SEVERITY OF COVID-19 AND IN CONDITIONS OF A CYTOKINE STORM - Stanislav B Putkov; Natalya V Davydova; Sergey P Kazakov (Медицинская иммунология, 2019)
AbstractToday, the clinical manifestations of COVID-19 patients range from mild to severe, especially in groups of patients susceptible to chronic diseases. The selection of the most informative indicators that provide a prognosis of the possible outcome or severe course of the disease in patients with COVID-19 is necessary at an early stage to determine effective treatment tactics. The earliest predictors of deterioration in patients with COVID-19 are elevated levels of interleukin-6, interleukin-10, C-reactive protein, procalcitonin, and other indicators of the innate immune system. One of the objectives of this study was to determine the most informative indicators of general clinical blood analysis and the main subpopulations of lymphocytes in patients with COVID-19, which can help in interpreting the severity of the disease and the development of a cytokine storm along with clinical manifestations and functional diagnostic methods. We conducted a retrospective cohort study of peripheral blood in 65 patients, of whom 57 were men and 8 were women, the age of the patients ranged from 32 to 82 years, the average age was 48.6 years. After examining the total blood count in 65 samples, cytometric analysis was performed using the Cytomics™ FC 500 series flow cytofluorometry system from Beckman Coulter (USA), CD45-ECD, CD3-FITC, CD4-PC7, CD8-PE, CD19-PC-5, CD16+56-PE monoclonal antibodies from "Beckman Coulter" (USA). Statistical processing of the research results was carried out in the IBM SPSS Statistics 26.0 program (IBM, USA). In the patients with COVID-19 examined by us, absolute lymphopenia is noted against the background of neutrophilosis at the initial medical treatment, which is expressed in an increase in the values of the neutrophil-leukocyte and leukocyte-T-lymphocyte indices. These indexes are quite informative and can be used in predicting disease risks. The determination of the most reliable indicators of cellular immunity, such as CD3+, CD3+CD4+, CD3+CD8+, CD3-CD16+CD56+ lymphocytes, in addition to a clinical blood test, can assess the features of the body's immune response to SARS–CoV-2 infection, help predict the severity of the disease, and make a decision to change treatment tactics if necessary.